Пятенная активность звезд движущихся групп по данным архива миссии TESS - Саванов, И. С.; Кондратьев, Н. Е.
On the base of TESS telescope archive data an analysis of the spot activity of stars of five selected moving groups, associations and clusters with ages from 10 to 425 million years was performed. The values of the rotation periods P, spottedness S, and the area of spots Aspot for 704 analyzed objects were obtained. Using the data under consideration evidence of the evolution of stellar activity over time was carried out. It is shown that the average level of spottedness of older stellar groups is lower than the average level of spottedness of younger ones. Quantitative estimates of the change in S of objects of the same age depending on their effective temperature are considered and presented. The obtained estimates of the S of solar-type stars of various ages (10-790 million years) with the spottedness of the Sun are compared.
Keywords: Астрофизика